PENERAPAN TEKNIK TOKEN ECONOMIC UNTUK MENINGKATKAN KEMAMPUAN MENJUMLAHKAN 0-50 AUTISTIK KELAS IV DI SKH AL KAUTSAR CILEGON BANTEN - Siti Dwi Jumiati; Dr. Hj. Isti Rusdiyani, M.Pd; Ratih Listyaningtyas, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
AbstractThis research is motivated by the low ability of children to add 0-50. The purpose of this study was to determine the increase in the ability to add 0-50 autistic children using the token economic. The research method used is the experimental method using the Single Subject Research (SSR) approach and using the A-B-A research design. The target behavior in this study is to add 0-50. The data collection technique in this study used a test given at baseline-1, intervention, and baseline-2 in 5 items. The data obtained were analyzed using analysis between conditions. Based on the results of the research data analysis, it was found that there was an increase in the ability to add 0-50 autictic children in class IV using the token economic behavior modification technique at SKh Al Kautsar Cilegon Banten. The results of the mean level in the baseline-1 were 43,33% and the increase after the intervention of token economic behavior modification tehnique was 74,17%. This shows that there is an increase in the ability to add 0-50 autistic children in class IV using the token economic behavior modification technique at SKh Al Kautsar Cilegon Banten.